Youth and drugs : report of a WHO study group. - WHO Study Group on Youth and Drugs (Geneva : World Health Organization, 1973)
Druggebruik bij de jeugd.
Includes bibliographical references.
Keywords: Adolescent; Drug abuse; Drug abuse; Substance-Related Disorders; Youth; Youth; Congresses